Kerkreg? Die plek van Kerkreg en Kerkregering - Wyk, Barry J. van (HTS teologiese studies, 2007)
Church polity? The position of church polity and church government It is generally accepted that John Calvin can be referred to as the founder of the presbyterial-synodal form of church government which is found in the Reformed Churches. It would therefore be appropriate to focus on his views and to indicate to what extent he influenced the notion that Jesus Christ is Head of the Church and Lord of the world. If it can once again be concluded that there is a close relation between Church, Confession and Church Ordinance, then it is quite evident that Church polity occupies a fundamental place in the Reformed Churches which must be treated with greater concern.